Intraspecific variations in leaf traits, productivity and resource use efficiencies in the dominant species of subalpine evergreen coniferous and deciduous broad‐leaved forests along the altitudinal gradient. (15th February 2021) - Hikosaka, Kouki; Kurokawa, Hiroko; Arai, Takahisa; Takayanagi, Sakino; Tanaka, Hiroshi O.; Nagano, Soichiro; Nakashizuka, Tohru
Abstract: Many studies have reported intraspecific variations in leaf functional traits, but their contribution to plant performance and ecosystem function are poorly understood. We studied altitudinal gradients of intraspecific variations in leaf traits, productivity and resource use efficiency in the dominant species of subalpine evergreen coniferous and deciduous broad‐leaved forests in Japan. We addressed three hypotheses, which are exclusive to each other. (1) Leaf traits vary along the leaf economics spectrum (LES). Plants that grow at lower and higher altitudes have fast‐ and slow‐return strategies, respectively, which improve productivity or resource use efficiency in the respective habitat. (2) Leaf trait variations are not consistent with the LES, but they contribute to improving productivity or resource use efficiency in the respective habitat. (3) Leaf trait variations do not contribute to improving productivity or resource use efficiency at higher altitudes. On the studied mountain range, Fagus crenata, a deciduous broad‐leaved tree, and Abies mariesii, an evergreen conifer, are the dominant species at lower and higher altitudes respectively. In F. crenata, leaf mass per area (LMA) and nitrogen concentrations were higher at higher altitudes. The net assimilation rate and light use efficiency during the growing season were greater at higher altitudes, which compensated for the shorter growing season in terms of annual productivity. In A. mariesii, the LMA was lower and the leaf life span was unchanged at higher altitudes. Productivity and resource use efficiency decreased with altitude. Synthesis . We conclude that F. crenata improves its productivity and resource use efficiency at higher altitudes by altering its leaf functional traits (Hypothesis 2), whereas alterations to leaf traits in A. mariesii are not associated with any improvement at higher altitudes (Hypothesis 3), which may result from the negative impact of environmental stress. Hence, the ecological significance of altitudinal variations in leaf traits depends on species and environment. Abstract : Fagus crenata had higher leaf mass per area and leaf N at higher altitude, which improved productivity and light use efficiency to compensate for the shorter growing season, whereas leaf trait alteration in Abies mariesii did not improve productivity and resource use efficiencies at higher altitude. The ecological significance of altitudinal variation in leaf traits depends on species and environment.